American government : - Lowi, Theodore J. (Norton, 2002)
This text presents a historical and institutional approach in discussing the American government. The seventh edition of "American Government: Power and Purpose" includes: increased attention to the analytic narrative; emphasis on fundamental, underlying principles of politics; and a critical examination of institutional reform. With meaningful pedagogy throughout the text and a multimedia instructional package, this text aims to lead students to analyze the core principles of politics and to understand how these principles influence American political devlopment